The other walls : the politics of the Arab-Israeli peace process - Saunders, Harold H. (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1985)
This book is not a history of past negotiations. Instead, it offers insights into the obstacles to peace in the future. It offers an original approach to overcoming the most formidable of all barriers-the one in the minds of those who negotiate. It is a book about the politics of human being living together. It is human story.
Includes bibliographies.
osa 22/01/19
Loans
Keywords: Israel-Arab War, 1973; Arab-Israeli conflict; Arab-Israeli conflict; Middle East